Discovering Our Gifts from Nature Now and in the Future. Part I - Cordell, Geoffrey A. (Pontificia Universidad Católica del Perú, 2002)
In the next article we will examine sorne aspects of traditional medicine, and the legal issues around natural product acquisition. Finally, in the third article, we will try to bring all of these issues together and present a rational approach to what needs to occur in the immediate future in order to have a coherent use of natural products for global primary health care 20-30 years from now.
Keywords: Química; https://purl.org/pe-repo/ocde/ford#1.04.00